Hsa_circ_103973 Acts as a Sponge of miR-335 to Promote Cervical Cancer Progression - Zhu, Yingping (Onco Targets Ther, 2020)
BACKGROUND: Cervical cancer (CC) ranks as the second most common malignancy in women, accounting for more two 2 million deaths every year in the world. Recently, circular RNAs (circRNAs) have been reported to regulate the progression of multiple human tumors; however, whether it involves in CC remains largely elusive. MATERIALS AND METHODS: Two GEO circRNA expression profiles (GSE102686, GSE113696) were downloaded to analyze the differentially expressed circRNAs using bioinformatics methods. Expression of circ_103973, miR-335 and PPP6C in CC tissues and cell lines were examined by qRT-PCR. Cell apoptosis was assessed with PI/Annexin-V double staining followed by the analysis of flow cytometry. Cell proliferation was evaluated by MTT and colony formation assays. Interaction between circ_103973 and miR-335, as well as miR-335 and PPP6C, were verified by dual-luciferase reporter assay. RESULTS: Circ_103973 was found to be highly expressed in both GSE102686 and GSE113696 datasets as well as in CC tissue samples and cell lines. Higher levels of circ_103973 were correlated to a worse outcome of CC patients. Knockdown of circ_103973 significantly promoted CC cell apoptosis and inhibited CC cell proliferation in vitro. Mechanistically, we demonstrated that circ_103973 served as a sponge of miR-335, which directly targeted PPP6C in CC cells. miR-335 was found to be decreased in CC, while PPP6C was found to be increased in CC. Moreover, anti-miR-335 could reverse the inhibitory effects of circ_103973 knockdown on CC cell proliferation, and this phenomenon could be blocked by si-PPP6C. CONCLUSION: Circ_103973 promoted CC cell proliferation in vitro by physically binding miR-335, which further targeted and regulated PPP6C.